Islam Populer sebagai Pencarian Identitas Muslim Kelas Menengah Indonesia - Raharjo Jati, Wasisto (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
This article aims to analyze the construction of identity in the case study of Middle-Class Muslim in Indonesia. The term ?Popular Islam? is part of an academic term to mention of make Islam as an identity for the Middle-Class Muslim in Indonesia. This term can be interpreted into two premises are popular Islam as a commoditization of Islamic value and Islam as part of celebration Islamic day. Both of these terms later then forked between Islamization and indigenization thus creating their assorted shades of Middle-Class Muslim in Indonesia. Consumption then present a cultural sign to distinguish the Middle Class. It was later manifested in the mass cultural products on behalf of Islam. That image displayed on consuming the product and then create construction of an Islamic Middle Class, religious Middle Class, and the Arabized Middle Class. This paper will elaborate more deeply about in search of identity and its impact to Middle-Class Muslim in Indonesia.